The Palgrave Handbook of National Security
XIII, 415 p. 3 illus., 1 illus. in color.
Keywords: This handbook provides a comprehensive analysis of the contemporary theory, practice and themes in the study of national security. Part 1: Theories examines how national security has been conceptualised and formulated within the disciplines international relations, security studies and public policy. Part 2: Actors shifts the focus of the volume from these disciplinary concerns to consideration of how core actors in international affairs have conceptualised and practiced national security over time. Part 3: Issues then provides in-depth analysis of how individual security issues have been incorporated into prevailing scholarly and policy paradigms on national security. While security now seems an all-encompassing phenomenon, one general proposition still holds: national interests and the nation-state remain central to unlocking security puzzles. As normative values intersect with raw power; as new threats meet old ones; and as newactors challenge established elites, making sense out of the complex milieu of security theories, actors, and issues is a crucial task - and is the main accomplishment of this book. Michael Clarke is Visiting Fellow at the Australia-China Relations Institute, University of Technology Sydney, Australia. Adam Henschke is Associate Professor at the University of Twente, The Netherlands. Tim Legrand is Associate Professor in the Department of Politics and International Relations, School of Social Sciences, University of Adelaide, Australia. Matthew Sussex is Adjunct Associate Professor at the Griffith Asia Institute, Griffith University, Australia.